Socio-Economic Reciprocity In Sagu Processing In Kwamor Ena Village, East Seram District, East Seram District - Misbahudin Mokan; Prof. Dr. Ir. AE Pattiselanno; Dr. JD Siwalette (Cita konsultindo, 2024)
Maluku is an archipelagic province located in eastern Indonesia. Maluku Province is known as an area that has abundant sago potential. This can be seen in the distribution and potential areas of sago in Maluku in terms of land area, namely in East Seram Regency covering an area of 36,075 ha, Central Maluku Regency covering an area of 6,425 ha, West Seram Regency covering an area of 8,410 ha . This research was carried out in Kwamor Ena Village, East Seram District. Eastern Seram Regency. The method used in this research is a descriptive method, namely a form of research intended to describe existing phenomena, both natural phenomena and man-made phenomena, these phenomena can be in the form of forms, activities, characteristics, changes, relationships, similarities and differences between phenomena. one with another. In simple terms, reciprocity is reciprocal exchange between individuals or between groups. These limits do not reveal the characteristics of the exchange actors. The pattern has laid the foundation for the meaning of reciprocity by showing the characteristics of the actors in the exchange. Reciprocity in the Kwamor Ena Village community regarding the farmer system in reciprocity they have been passed down from generation to generation so that knowledge is passed down from generation to generation. The increasingly developed education has made the community's mindset aware of how important education is for their children, so the Kwamor Ena Administrative Village community tries to provide education. the best for their children. The prevailing customs in the form of circumcision marriages are still adhered to today. The Kwamor Ena Administrative Village is still well accepted and implemented from generation to generation from their ancestors.